AIRCRAFT EMISSION ESTIMATION UNDER OPERATIONAL CONDITIONS IN THE AIRPORT AREA - Synylo, Kateryna (Proceedings of National Aviation University (archive), 2015)
The arcticle represents the results of the analysis of aircraft engine emissions measurement principles and techniques, which were implemented on the ground of measurement campaigns at major European airports. The paper is devoted to investigation of operational and meteorological conditions impact on emission indexes of aircraft engine. On the ground of analysis of CFM56-5С2 engine test for cruise and idle conditions was observed, that real operational conditions differ from certificated ones. The observed variations between determined and certificated emission indexes are most likely caused by operational (thrust) and meteorological (air temperature and humidity) conditions under real circumstances which are quite different from well defined conditions during certification procedure. Determination of emission indexes under real operational (real value of thrust) and meteorological (ambient temperature) conditions is an actual task, as input data for models and high accurate assessment of aircraft emissions contribution to total air pollution in the vicinity of airport. In addition, estimation emission indexes with taking into account engine age and its maintenance, allow to calculate precisely the emission inventories of airports.